Cause-related marketing, legitimacy and internationalization of professional service firms: A case study of a football talent scouting microfirm. Issue 5 (24th January 2020) - Arslan, Ahmad; Golgeci, Ismail; Haapanen, Lauri; Tarba, Shlomo; Cooper, Cary; Degbey, William Y.
Abstract : Purpose: The purpose of this paper is to address the role of legitimacy in internationalization to Africa of a Finnish professional service microfirm, which uses cause-related marketing (CRM) as the business model. Design/methodology/approach: The paper consists of a single case study of a microfirm (two employees) originating from Finland, which has successfully internationalized to many African countries. Due to the uniqueness of the context, the authors use semi-structured interviews to collect founders' insights to the issue being addressed. Moreover, along with interviews, secondary sources related to football talent scouting in Africa are also utilized in the paper. Findings: The authors found that the case company was established with the aim of helping and uplifting poor African footballers, so the business model is CRM. It has scouted many of them for professional football clubs in Europe. The authors further found that sociopolitical legitimacy plays a major role in dealing with African footballers and local stakeholders, while cognitive legitimacy helped the case firm gain the trust of European football clubs. Originality/value: Internationalization of microfirms operating in the service sector is a rather under-researched area compared to the internationalization of SMEs and large MNEs. The paper is one of the first to study internationalization of a professional service microfirm involved in scouting football talent in Africa and matchmaking them with European football clubs. It contributes to extant CRM and internationalization literature by being one of the first to analyze a firm whose business model revolves around CRM and discussing specific roles of different kinds of legitimacies needed for internationalization to Africa in this specific service sector.